Examining the impact of leadership styles on teacher effectiveness: A structural equation modeling and multiple regression - Liang Mingyu; Mohd Khairuddin Abdullah @Jerry Abdullah; Connie Shin @ Connie Cassy Ompok (Human Resource Management Academic Research Society, 2025)
This study examines the influence of transformational and transactional leadership on teacher effectiveness among young teachers in private universities in Shandong Province, China. Motivated by the demand for high-quality education, this study seeks to address a research gap in leadership’s role in the professional development of early-career teachers in Chinese private universities. Using a quantitative research method, data was collected from 416 teachers and analyzed through structural equation modeling (SEM) and multiple regression analysis. The findings indicate that both leadership styles significantly impact teacher effectiveness, with transactional leadership (β=0.582) exhibiting a slightly stronger effect than transformational leadership (β=0.487). Among transformational leadership dimensions, Intellectual Stimulation (IS) had the most significant influence, whereas Contingent Reward (CR) was the strongest predictor within transactional leadership. However, Idealized Influence (II) and Individualized Consideration (IC) had no significant impact on assessment and learning environment within teacher effectiveness, respectively. This study contributes to the existing literature by offering empirical insights into the relationship between leadership and teacher effectiveness in the context of Chinese private universities. It also provides practical implications for educational management, advocating for a balanced integration of both leadership styles to optimize teacher performance. Future research should explore cultural factors that may impact these relationships.